Fatal, non-fatal burden of cancer in the elderly in China, 2005-2016: a nationwide registry-based study - Zhen-Rong Ma; Kang-Qian Lin; Hong Guo; Kai-Yue Yang; Miao Cao; Xi Song; Huai-Miao Jia; Yun-Hua Hu; Yi-Zhong Yan (BMC, 2023)
Abstract Background As populations age, cancer burden becomes increasingly conspicuous. This study quantified the cancer burden of the elderly (≥ 60 years) in China, based on the China Cancer Registry Annual Report to provide epidemiological evidence for cancer prevention and control. Methods Data on cancer cases and deaths among the elderly aged ≥ 60 years were collected from the China Cancer Registry Annual Report, 2008-2019. Potential years of life lost (PYLL) and disability-adjusted life years (DALY) were calculated to analyze fatalities and the non-fatal burden. The time trend was analyzed using the Joinpoint model. Results From 2005 to 2016, the PYLL rate of cancer in the elderly was stable between 45.34‰ and 47.62‰, but the DALY rate for cancer decreased at an average annual rate of 1.18% (95% CI: 0.84-1.52%). The non-fatal cancer burden in the rural elderly was higher than that of the urban elderly. Lung, gastric, liver, esophageal, and colorectal cancers were the main cancers causing the cancer burden in the elderly, and accounted for 74.3% of DALYs. The DALY rate of lung cancer in females in the 60-64 age group increased (annual percentage change [APC] = 1.14%, 95% CI: 0.10-1.82%). Female breast cancer was one of the top five cancers in the 60-64 age group, with DALY rates that also increased (APC = 2.17%, 95% CI: 1.35-3.01%). With increasing age, the burden of liver cancer decreased, while that of colorectal cancer rose. Conclusions From 2005 to 2016, the cancer burden in the elderly in China decreased, mainly reflected in the non-fatal burden. Female breast and liver cancer were a more serious burden in the younger elderly, while colorectal cancer burden was mainly observed in the older elderly.